4.4-1.8+(-2.4)-(3.6)-2.8 =4.4-2.4-(1.8+2.8+3.6) =2-8.2 =-6.2
4.4-1.8+(-2.4)-(3.6)-2.8=?
2个回答
相关问题
-
1*3+2*6+4*12/2*4+4*8+8*16
-
2*3+4*6+6*9+8*12分之1*2+2*4+3*6+4*8
-
1*2+2*4+3*6+4*8分之2*3+4*6+6*9+8*12
-
(1*1+2*4+3*6+4*8)除以(2*3+4*6+6*9+8*12) 简便计算
-
4√6-4√1/2+3√8
-
数独 2 7 9 4 9 8 1 6 7 3 8 4 5 3 2 6 2 9 6 7 4 3 4 5 1 7 2 8 6
-
7 1 5 4 3 19 3 6 8 6 3 2 6 9 81 8 41 6 9 9 2 4 4 8 2
-
6+8-2+2-3-1+4-4/1-2
-
(1.2*3.6*10.8+2*6*18+13/1*13/3*13/9)除以(1.2*2.4*4.8+2*4*8+13/
-
(1*2+2*4+3*6+4*8+...+101*202)/(2*3+4*6+6*9+8*12+...+202*203)